Development of a “passive” cut-off system of final bof slag and prodused of functional stopers - Kamkina , L.V.; Smirnov , O.M.; Sharandin , K.M.; Ryabyi , D.V. (Theory and Practice of Metallurgy, 2024)
One of the main tools for improving the quality of produced metal products is operations to detect and cut-off slag during the technological metal transfer from BOF to the ladle. According to estimates from various researchers and practical experience, the amount of slag entering the ladle during the tapping is distributed as follows: up to 25% - at the beginning, up to 60% - at the end of the tapping and up to 15% - when the converter returns to its working position. Today, there are two basic schemes for cutting off converter slag: automatic (“active”) and “passive”. The main automatic schemes include a “gas-dynamic” cut-off system and a “slide gate” type system. An affordable and effective alternative is the scheme of “passive”, primary and secondary BOF slag cut-off system, using functional refractory devices. At the industrial facilities of GIR-Engineering LLC, together with PTIMA NAS of Ukraine, has developed a "passive" scheme for the complex BOF slag cut-off system. It includes two systems, primary cut-off with a plastic “tampon” type stopper and secondary cut-off with the refractory “ball” / “dart” type stopper. Both systems work with manual applicators, which minimizes the capital costs of introducing them into the production chain. During the period from July 2020 to September 2020, successful experimental and pilot-industrial tests of primary cut-off slag stoppers “tampon” type, “GIR-TAMP-150-DMK” brand, were carried out in steelmaking shop of PrJSC “KAMET-STAL” (Kamianske, Ukraine) consisting of two 250-ton capacity BOF units. The average rephosphorization rate using the developed products was reduced by 20%. During 2021-2024 years, at the PrJSC " KAMET-STAL" plant, successful industrial tests of the developed complex BOF slag cut-off system were carried out. The total economic effect from implementation was ≈ 1.2 USD per ton of steel.